Pulmonary Artery Hypertension in Acyanotic Congenital Heart Disease Underwent Transcatheter Closure at Dr. Soetomo Hospital - I Ketut Alit Utamayasa1 , Mahrus A Rahman1 , Taufiq Hidayat1 , Teddy Ontoseno1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Pulmonary artery hypertension (PAH) is common complication of congenital heart disease.Echocardiography before and after transcatheter closure procedure is needed for further evaluation.Objective: To evaluate the PAH before and after transcatheter closure procedure by echocardiography atDr. Soetomo Hospital.Methods: Medical record patients with acyanotic congenital heart disease with PAH and already donetranscatheter closure procedure in 2010 – 2014 were reviewed. Data taken were demographic, clinical,and echocardiography. Tricuspid regurgitation pressure gradient (TRPG) was evaluated. Statistical analysisusing t test comparative study; P<0.05 was considered significant.Results: There were 46 patients underwent transcatheter closure, ASD closure 22/46, VSD closure 16/46,PDA closure 8/46 patients. Ten patients with PAH (10/46), 4/10 ASD, 4/10 PDA and 2/10 VSD. Boys were6/10, median age was 60 (range 4-144 months). Median TRPG before procedure was 32.4 (range 25-43mmHg). Median TRPG after procedure was 21.5 (range 15-26.9 mmHg). There was significant decreased inPAH after transcatheter closure procedure (P=0.01).Conclusion: Transcatheter closure procedure in acyanotic congenital heart disease was important fordecreasing the pressure gradient of PAH.